Medicinal Plant Images - Cock, Ian Edwin (Asian Journal of Biological and Life Sciences)
Grevillea flowers were used as a food source by Australian Aborigines. The flowers were sucked for their sweet nectar or used to make sweet drinks.1 They also had roles as traditional bush medicines for Australian Aborigines. The leaves of several species were used to treat wounds and sores, skin diseases as well as diarrhoea and dysentery.1,2 Many of these diseases are caused by bacterial pathogens. Grevillea spp. decoctions were also used as potent bacteriocides and are reputed to have broadspectrum inhibitory activity.6,7 Unfortunately most of our understanding of the antimicrobial potential of Australian Grevillea species is anecdotal, with few species being thoroughly studied. Indeed, we were only able to find two studies that have examined Grevillea spp. extracts for antibacterial activity.3,4 Unfortunately, both of these studies screened for antibacterial activity using a single, relatively high extract concentration and did not determine MIC values, making it impossible to benchmark the efficacy of these extracts against other plant species and conventional antibiotics. More recently, studies have reported antibacterial activity for Grevillea juncifiolia Hook. and Grevillea robusta A. Cunn. ex R. Br. (thepictured species)